Pattern of Causative Micro-organism in Catheter Related Blood Stream Infections in Patients Receiving Hemodialysis through Venous Catheter in Combined Military Hospital, Dhaka - Uddin, Md. Salim; Rahman, A K M Mijanur (Journal of Armed Forces Medical College, Bangladesh, 2026)
Background: Catheter Related Blood Stream Infections (CRBSI) is an important frequently encountered abnormality in clinical medicine in patients receiving hemodialysis (HD) through venous catheter. It is the most prevalent vascular access device complication in both the hospital and home setting which is increasing markedly in patients undergoing HD through venous catheter, though the result varies from different institutions and centers. Objective: To determine the incidence and isolate different types of micro-organism in individual receiving HD through venous catheter and to emphasize in putting a protocol to decrease CRBSI. Methods: The study was an observational type of cross-sectional study that was conducted at the dialysis center of nephrology ward in Medicine in Combined Military Hospital (CMH), for six months from June 2019 to November 2019. A total number of 100 suspected CRBSI patients of different age group receiving HD through venous catheter participated. The participants were informed about the nature and purpose of the study and written consent were given by patients themselves. After collecting samples with aseptic procedure, data was analyzed by the SPSS v23.0. Results: Among 100 participants, age ranging from 40 to 90 years. Mean age was 64.86±25.1 years. Participants were both male and female. There were 41 distinct episodes of CRBSI. Gram-negative micro-organisms were 75.6% (n=31) and 24.4% (n=10) were due to gram-positive micro-organisms. Twenty cases were- Pseudomonas aeruginosa, S aureus 9. Klebsiella 6, Escherichia coli 2, Acinetobacter spp 2, Burkholderia cepacia complex 1 & MRSA 1. CRBSI was isolated mostly in males (n=29), diabetics (n=33), in age 40-74 years (n=30) and patients with temporary venous catheters. Conclusion: Gram-negative micro-organisms were major causes of CRBSI in this study. Pseudomonas aeruginosa is the key among them, a finding not observed in other studies. Staph aureus is next micro-organism responsible for CRBSI, that is also a common fact in worldwide. Diabetes mellitus, old age, male gender, temporary &prolonged duration of venous catheter group was highly associated with CRBSI incidence. JAFMC Bangladesh, Vol 21, No 2 (December) 2025:49-52